PENGARUH COGNITIVE BEHAVIOUR THERAPY TERHADAP TINGKAT KECEMASAN PASIEN PRE OPERASI - Davita S Batoek; Harianti Fajar (Pasapua Health Journal, 2019)
Introduction : Surgical procedures will cause a variety of emotional reactions for patients who will undergo one of the reactions that arise is anxiety. Non-pharmacological anxiety management cognitive behavioral therapy can be used to reduce anxiety levels. The purpose of this study was to determine the effect of cognitive behavioral therapy on preoperative patient anxiety levels. Method : The research design used was a pre experimental design with the static group comparison approach: randomized control group only. The population is all preoperative patients in Ambon Al-Fatah Hospital. Sampling using accidental sampling technique. The sample in this study amounted to 30 people who were divided into 15 people for groups who were given cognitive behavior therapy (intervention groups) and 15 people for groups that were not given cognitive behavior therapy (control groups). Result :The results of the study were obtained from 30 respondents where the level of anxiety in preoperative patients at Al-Fatah Hospital in Ambon in 2019, after being given cognitive behavior therapy in the intervention group, namely there is no anxiety scale 0-13 (86.7%) and mild anxiety scale 14-20 (13.3%), whereas in the mild anxiety control group a scale of 14-20 (33.3%), (46.7%) moderate anxiety scale 21-28 (46.7%), and severe anxiety scale 28-41 (20.0%). From the results of data analysis using the independent t statistic test, p value = 0,000 <0.05. Conclution : There is an influence of cognitive behavioral therapy on the level of anxiety of preoperative patients in Ambon Al-Fatah General Hospital. It is recommended to nurses to be able to use this non-pharmacological anxiety management to reduce the level of anxiety of preoperative patients.